Maternal Exit from Employment after Premature Birth - Taylor, Katherine D.; Rickenbach, Olivia Nieto; Syed, Aliba; Tumin, Dmitry (American Journal of Perinatology, 2025)
We sought to evaluate whether infants' preterm birth (PTB) or low birth weight (LBW) were associated with maternal exit from employment after birth.We analyzed data from the National Longitudinal Survey of Youth 1979 cohort, tracking maternal employment after each birth. Births were included if the mother was working at the beginning of the birth month. Time to exit from paid employment (becoming unemployed or leaving the labor force) was tracked up to 2 years after birth.Of 2,647 births to cohort members, 243 infants were born preterm (13%) and 192 were LBW (7%). On multivariable Cox regression, LBW was independently associated with 34% greater hazard of maternal exit from employment (hazard ratio: 1.34; 95% confidence interval: 1.08, 1.66; p = 0.007).LBW, but not PTB, was independently associated with increased risk of maternal exit from employment.
Keywords: preterm birth; maternal employment; birth weight; premature infants